Jawabanmu

2014-04-19T08:41:26+07:00
Tentukan y' dari y=(3X²-1) (X+5)³
                        y= 3x²-1 (x² + 10x +25)(x +5)
                         =(3x²-1)(x³ +5x² +10x² +50x + 25x +125)
                        = (3x² -1)(x³ +15x² +75x+125)
                        =3x⁵ +45x⁴+ 225x³+ 375x² - x³ -15x²-75x -125
                        =3x⁵ +45 x⁴ +224x³ +360x² -75x -125


y'  = 15x⁴+180x³ +672x² +720 x-75

mohon dicek kembali 
semoga membantu =)
bagaimana kalo pake rumus f '(x) = u' v + u v' ? kepanjangan ya, hmm